Do students need teacher written corrective feedback? A Case Study at Secondary School - Dyah Fitri Mulati (Universitas Muhammadiyah Semarang, 2018)
This study was designed as a case study surveying thirteen students from secondary school as the research participants. The purpose of this current study is to explore ESL students‟ views toward the existence and the need of teacher written corrective feedback on their writing class. An openended questionnaire comprised seven questions adapted from Diab (2005) was employed to gather the data. The finding denotes that the participants have positive views toward written corrective feedback on their writing class even though some researchers, led by Truscott in 1996, believe that written corrective feedback is even harmful for the students. This result points to several pedagogical implications that would be discussed on the paper.